TP53 mutation at early stage of colorectal cancer progression from two types of laterally spreading tumors. Issue 6 (27th April 2016) - Sakai, Eiji; Fukuyo, Masaki; Matsusaka, Keisuke; Ohata, Ken; Doi, Noriteru; Takane, Kiyoko; Matsuhashi, Nobuyuki; Fukushima, Junichi; Nakajima, Atsushi; Kaneda, Atsushi
Abstract : Although most sporadic colorectal cancers (CRC) are thought to develop from protruded adenomas through the adenoma–carcinoma sequence, some CRC develop through flat lesions, so‐called laterally spreading tumors (LST). We previously analyzed epigenetic aberrations in LST and found that LST are clearly classified into two molecular subtypes: intermediate‐methylation with KRAS mutation and low‐methylation with absence of oncogene mutation. Intermediate‐methylation LST were mostly granular type LST (LST‐G) and low‐methylation LST were mostly non‐granular LST (LST‐NG). In the present study, we conducted a targeted exon sequencing study including 38 candidate CRC driver genes to gain insight into how these genes modulate the development of LST. We identified a mean of 11.5 suspected nonpolymorphic variants per sample, including indels and non‐synonymous mutations, although there was no significant difference in the frequency of total mutations between LST‐G and LST‐NG. Genes associated with RTK/RAS signaling pathway were mutated more frequently in LST‐G than LST‐NG ( P = 0.004), especially KRAS mutation occurring at 70% (30/43) of LST‐G but 26% (13/50) of LST‐NG ( P < 0.0001). Both LST showed high frequency of APC mutation, even at adenoma stage, suggesting its involvement in the initiation stage of LST, as it is involved at early stage of colorectal carcinogenesis via adenoma‐carcinoma sequence. TP53 mutation was never observed in adenomas, but was specifically detected in cancer samples. TP53 mutation occurred during development of intramucosal cancer in LST‐NG, but during development of cancer with submucosal invasion in LST‐G. It is suggested that TP53 mutation occurs in the early stages of cancer development from adenoma in both LST‐G and LST‐NG, but is involved at an earlier stage in LST‐NG. Abstract : We conducted targeted exon sequencing study of flat, early colorectal lesions, so‐called laterally spreading tumors (LSTs), to gain insight into involvement of molecular alterations in progression of colorectal cancer through de novo pathway. APC mutation was frequently involved by adenoma stages in both granular‐type LST (LST‐G) and non‐granular LST (LST‐NG), suggesting its involvement in tumor initiation in LSTs. TP53 mutation was involved during cancer development from adenoma to cancer for both LST‐G and LST‐NG, but was involved at earlier stage in LST‐NG.